Lang wirksames Wachstumshormon – eine neue Therapieoption für Kinder mit Wachstumshormonmangel: Status 2024 - Dörr, Helmuth-Günther; Bettendorf, Markus; Wölfle, Joachim; Saenger, Paul; Ranke, Michael B. (Monatsschrift Kinderheilkunde, 2024)
Until recently, daily singular subcutaneous injections of recombinant human growth hormone (rhGH) was the treatment of choice in short-statured children with growth hormone deficiency (GHD). This concept has been effective and safe for almost four decades; however, with this practice of replacement therapy approximately 10–20% of the children did not reach an adult height within the target range of the parents. Among the various factors involved, insufficient adherence, as the consequence of the necessary but inconvenient daily injections has been identified as a particularly important factor. This prompted the development of long-acting growth hormone (LAGH). At the end of 2023 there were three approved LAGH preparations available in Germany for the treatment of children older than 3 years with GHD due to an insufficient secretion of GH. All approved LAGH formulations use different technologies to prolong the half-life of rhGH. The LAGH as well as rhGH bind to the GH receptor and initiate the signal cascade that leads to the activation of growth and metabolism. In phase 3 studies LAGH showed non-inferiority to daily rhGH injections in terms of increasing height as well as comparability in the safety profiles. Thus, the treatment with LAGH offers a new option for children and adolescents with GHD; however, the long-term efficacy and safety need further systematic evaluation. Parents and patients need to be informed about all relevant aspects of the new treatment. This review article discusses the currently approved LAGH preparations in Germany together with the published data from a pediatric perspective.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Adherence; Lonapegsomatropin; Somapacitan; Somatrogon